2008
DOI: 10.1364/oe.16.016711
|View full text |Cite
|
Sign up to set email alerts
|

Time fluctuations of the phase modulation in a liquid crystal on silicon display: characterization and effects in diffractive optics

Abstract: Abstract:In this paper we provide evidence of the temporal fluctuations of the phase modulation property of a liquid crystal on silicon (LCoS) display, and we analyze its effect when the device is used for displaying a diffractive optical element. We use a commercial twisted nematic LCoS display configured to produce a phase-only modulation, and we provide time resolved measurements of the diffraction efficiency that show rapid fluctuations of the phase modulation, in the millisecond order. We analyze how thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
92
0
7

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 149 publications
(100 citation statements)
references
References 26 publications
(48 reference statements)
1
92
0
7
Order By: Relevance
“…The combination of high quality imaging, low-excitation power, and low background makes the IMPACT based superpenetration optical microscope a promising tool for a broad range of biomedical applications. In particular, it paves the way for intravital functional and dynamic imaging at unprecedented depth beneficial for in vivo studies involving highly turbid samples including, but not limited to, neuroscience (33) and immunology (34,35).…”
Section: Resultsmentioning
confidence: 99%
“…The combination of high quality imaging, low-excitation power, and low background makes the IMPACT based superpenetration optical microscope a promising tool for a broad range of biomedical applications. In particular, it paves the way for intravital functional and dynamic imaging at unprecedented depth beneficial for in vivo studies involving highly turbid samples including, but not limited to, neuroscience (33) and immunology (34,35).…”
Section: Resultsmentioning
confidence: 99%
“…This reasoning is not restricted to PA-LCoS devices, but it can be applicable, in general, to electrooptic variable linear retarders, such as the novel device proposed by Ramirez et al 16 Different measurement methods have been proposed and demonstrated to characterize the phase-shift versus voltage in LCDs and LCoS devices. 12,17,18 Among these methods, the diffractive-based technique used by Lizana et al in Refs. 12 and 17 allow for instantaneous phase-shift values measurement.…”
Section: Introductionmentioning
confidence: 99%
“…However, due to experimental imperfections of the optical elements in the set-up (see Fig. 3) with respect to the theoretical values (caused by non-zero retardance values of the beam-splitters [27], certain experimental offset for the waveplates orientation, time-fluctuations of the phase introduced by the LCOS display [28], etc. ), the above mentioned phase encoding procedure may lead to slightly modified results.…”
Section: Resultsmentioning
confidence: 99%